A dynamic multi-dimensional trust evaluation model to enhance security of cloud computing environments. (1st January 2011) - Sun, Dawei; Chang, Guiran; Sun, Lina; Li, Fengyun; Wang, Xingwei
High security of cloud computing is one of the most challenges to be addressed before the novel pas-as-you-go business paradigm is widely applied over the internet. Trust brings a novel means to improve the security of cloud computing platforms. However, there are few systematic works on trust in cloud systems. In this paper, the definition of trust in cloud systems is given and the properties of trust are analysed by referring to the fruits from social science. Based on the properties and semantics of trust, a dynamic multi-dimensional trust model named DMTC is proposed, which includes a time-variant comprehensive evaluation multi-dimensional method for expressing direct trust and a space-variant evaluation multi-dimensional method for calculating recommendation trust. To compute trust in cloud systems, an algorithm based on the DMTC model is given. Experiment results show that the proposed model can dynamically and effectively construct the trust relationship in cloud computing environment.